Analysis of Fluoride Concentration in Toothpastes in the United Arab Emirates: Closing the Gap between Local Regulation and Practice - Ammar Abdulrahman Jairoun; Sabaa Saleh Al-Hemyari; Moyad Shahwan; Obaida Jairoun; Sa’ed H. Zyoud (Cosmetics, 2021)
Background: While there is much scientific evidence supporting the benefits of fluoride for oral health, the concentration of fluoride in over-the-counter fluoride toothpaste should meet United Arab Emirates (UAE) regulations of a fluoride concentration not exceeding 0.15%. Objectives: The current study examines the fluoridated toothpaste products available on the UAE market and aims to quantify their total fluoride content. Methods: A total of 50 toothpaste products were collected and analyzed in this study. Ion Chromatography (IC) conductivity analysis was performed to determine the total fluoride content. Results: Among the 50 products tested, 10 exceeded the recommended concentration of total fluoride of less than 0.15%, while 12 had a total fluoride concentration that was less than was declared on their labels. Moreover, this study has revealed that 22 of the sampled products had a total fluoride concentration below 1000 ppm fluoride. An increased risk of higher total fluoride content was observed in the toothpaste products with monofluorophosphate active ingredients than in products with potassium nitrate/sodium fluoride and sodium fluoride (p = 0.011). Conclusions: There is a need to reassess the effectiveness of current regulations in the UAE to ensure that all fluoridated toothpastes available on the market are safe and effective for the consumer. Specifically, appropriate guidelines should be established on the basis of the risks and benefits inherent in fluoride exposure. Moreover, fluoridated toothpastes need to be subject to stricter monitoring and control regarding their safety and quality through good manufacturing practices (GMPs), education, research, and adverse event reporting.